DYNAMICS OF DEMAND FOR HIGHER EDUCATION IN JAMBI PROVINCE: THE ROLE OF PER CAPITA INCOME AND POPULATION IN A PANEL DATA FRAMEWORK 2018–2022 - Kuswanto; Lukitatary Pramessariarda, Aisyah; Refnida, Refnida (Edunomika Journal: Studies in Education and Development Economics, 2026)
Public interest in improving their quality of life through higher education continues to grow, as evidenced by the rapid growth of private universities. However, access to higher education remains unequal, particularly in rural areas. This study aims to examine the extent to which demand for higher education in Jambi Province is influenced by per capita income and population growth. Using a panel data design, this study analyzes data from 2018–2022 from six districts/cities in Jambi. The data were processed using panel data regression with the help of EViews 12 software. The model selection process (through the Chow, Hausman, and Lagrange Multiplier tests) showed that the Common Effect Model (CEM) was the most appropriate predictor for the data and research objectives. Empirically, the test results show that per capita income has a positive and significant effect on the demand for higher education. This indicates that increased economic capacity drives preference for higher education opportunities. Furthermore, population growth also has a substantial impact on the demand for higher education, confirming that demographic dynamics influence the public’s need for access to this level of education. These findings indicate that the public tends to view higher education as an important means of improving living standards, both socially and economically. Therefore, higher education policies need to consider responses to income variations and demographic dynamics to ensure equitable access and improve the quality of human resources in Jambi Province.